Exploring the potential for pharmacist prescribing in the management of hypertension in primary care: an Australian survey. (10th May 2017) - Bajorek, Beata; Krass, Ines
Abstract: Background: The management of hypertension, particularly medicines use, remains suboptimal and pharmacist‐delivered models of care may assist clinicians in this regard. Aim: The primary objective of this study was to explore the potential for pharmacists to make treatment recommendations and prescribing decisions for patients with hypertension. Method: Accredited (medicines review) pharmacists working in the primary care setting within the Sydney metropolitan area (NSW, Australia) were recruited. Pharmacists completed a scenario‐based survey that asked them to demonstrate a simulated prescribing function in the management of 6 patient scenarios. The management of the scenarios was assessed from the pharmacists' perspective (i.e. usefulness of prescribing, confidence in prescribing) and by an expert clinical panel (i.e. clinical appropriateness). Results: Thirty pharmacists (27.4 ± 10.7 years in practice) participated. Most pharmacists indicated that a prescribing function would be useful within their scope of practice and that they would be confident in executing this as an intervention. The expert clinical panel rated the vast majority of recommendations by pharmacists to be appropriate. Ratings for usefulness of, confidence in and appropriateness of the prescribing recommendations were lowest for the 2 scenarios depicting more complex cases; here the level of agreement among the expert panel was also poor (κ ≤ 0.15). Recommendations relating to processes for assessing patients were rated relatively lower, particularly for the complex scenarios. Conclusion: Accredited pharmacists have the capacity and potential for a prescribing function to help optimise hypertension management. Simulated prescribing interventions undertaken by accredited pharmacists were assessed as clinically appropriate by medical clinicians.